PyDEM: A generalized implementation of the inductive design exploration method. (15th November 2017) - Kern, Paul C.; Priddy, Matthew W.; Ellis, Brett D.; McDowell, David L.
Abstract: The emergence of multiscale design of materials and products has necessitated development of inductive robust design methods to rapidly develop and deploy new material systems. In addition, practical applications require robust designs which ensure performance goals are satisfied while accounting for model, noise, and control factor uncertainties. Recognizing the utility of a robust platform for design exploration, the Python Design Exploration Module (pyDEM) has been developed. The purpose of this work is to present this improved, generalized implementation of the Inductive Design Exploration Method (IDEM) to support integrated multiscale materials, process, and product design. The capabilities of pyDEM are highlighted and demonstrated via two test cases: (i) four-level Ultra High Performance Concrete (UHPC) panel and (ii) wire electric discharge machining (WEDM) process of titanium. Graphical Abstract: Highlights: An extended implementation of the Inductive Design Exploration Method for multilevel robust design of hierarchical materials. The IDEM framework is scripted via Python (pyDEM) to allow for widespread adaption and further alterations/modifications. Extended for disjoint and nonconvex feasible design spaces that satisfy ranged sets of performance requirements. Two test cases demonstrate the capability of pyDEM: (i) four-level UHPC panel, and (ii) WEDM process of titanium.